2013
DOI: 10.1111/ped.12125
|View full text |Cite
|
Sign up to set email alerts
|

Dexibuprofen for fever in children with upper respiratory tract infection

Abstract: Dexibuprofen (3.5 or 7 mg/kg) is as effective and tolerable as ibuprofen for fever caused by upper respiratory tract infection in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…7 and Table 4 ). We also found that genes in the network, such as PTGS2 and PTGS1, are targeted by a variety of nonsteroidal anti-inflammatory drugs (NSAIDs), including dexibuprofen, mefenamic acid, and bufexamac to improve symptoms of fever, rash, and insomnia 67 – 69 . It is similar and biomedical meaningful for the other 4 insomnia-related symptom clusters.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…7 and Table 4 ). We also found that genes in the network, such as PTGS2 and PTGS1, are targeted by a variety of nonsteroidal anti-inflammatory drugs (NSAIDs), including dexibuprofen, mefenamic acid, and bufexamac to improve symptoms of fever, rash, and insomnia 67 – 69 . It is similar and biomedical meaningful for the other 4 insomnia-related symptom clusters.…”
Section: Resultsmentioning
confidence: 96%
“…In our study, most of the symptoms with gene associations belong to the nervous system, which would be result in certain deviations. However, the 341 symptoms in our work have covered 180 (46.63%) of symptoms in Medical Subject Heading vocabulary 67 which was created and updated annually by the NLM since 1960s. This means that our results would deliver some kinds of reliable and useful knowledge for understanding the network mechanisms of the whole spectrum of symptom phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Tables 2 and 3 present the results of each of these studies. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 …”
Section: Resultsmentioning
confidence: 99%
“…Dexibuprofen and acetaminophen are the two most widely used antipyretic drugs in the pediatric population. The former is an enantiomer of racemic ibuprofen, an effective and tolerable antipyretic and analgesic drug for pediatric use [ 12 – 14 ], and an equal effect at a lower dose than ibuprofen has been shown in previous studies [ 15 17 ], some including pediatric upper respiratory tract infection (URTI) patients presenting with fever [ 18 , 19 ]. Acetaminophen is another popular choice of pediatric antipyretic drug, which is generally administered via oral route.…”
Section: Discussionmentioning
confidence: 99%